Microtunneling and horizontal drilling - (FSTT), French Society for Trenchless Technology (London Wiley-ISTE, 2006)
This book includes recommendations prepared by members of the French Society for Trenchless Technology (FSTT), based on their recent national multi-year project. Comprehensive guidelines, techniques and theories in the areas of both microtunneling and horizontal drilling are given, encompassing the fields of application for each method, what investigations should be undertaken, which machines and equipment should be used, how the work should be managed and potential problems that may arise. The recommendations, the analytical methods used and their verification with laboratory and field data should not only improve the rate of success of trenchless projects, but will also be of great value to engineers in other countries, who can compare the results with their own findings and assess the international state of the art.
Keywords: Trenchless construction -- Tunneling